Inhibition of High K+-Induced Contraction by the ROCKs Inhibitor Y-27632 in Vascular Smooth Muscle: Possible Involvement of ROCKs in a Signal Transduction Pathway - Kazuyuki Sakamoto; Masatoshi Hori; Masanori Izumi; Tatsuya Oka; Kazuhiro Kohama; Hiroshi Ozaki; Hideaki Karaki (Elsevier, 2003)
In the isolated rat aorta, a ROCKs (rhoA-dependent coiled coil serine/threonine kinases) inhibitor, Y-27632, inhibited the contractions induced not only by receptor agonists but also by high K+ with the similar IC50 values (0.8 - 4.9 μM). However, Y-27632 did not inhibit the increment of cytosolic Ca2+ concentration ([Ca2+]i) due to these stimulants. The Y-27632-induced inhibition of contraction was accompanied by an inhibition of myocin light chain (MLC) phosphorylation, although inhibition of contraction was stronger than that of MLC phosphorylation during the initial phase of contraction. Y-27632 had no effect on the myocin light chain kinase (MLCK) activity. This inhibitor also did not directly change the phosphatase activity. These results suggest that Y-27632 is a selective inhibitor of ROCKs with no direct inhibitory effect on [Ca2+]i, calmodulin, MLCK, or phosphatase. Y-27632 disrupted the actin filament network and decreased the filamentous actin, implying that the stronger inhibition by Y-27632 on early phase of contraction than MLC phosphorylation may be explained by this effect. These results suggest that the high K+-induced MLC phosphorylation and contraction are mediated not only by the classical Ca2+/calmodulin-dependent MLCK system but also by a novel MLC phosphorylation pathway involving ROCKs. One of the possibilities is that high K+ activates ROCKs to inhibit myosin phosphatase resulting in an augmentation of MLC phosphorylation and contraction.